Media Usability and Advancement of Regional Political Agenda in West Africa: Appraising knowledge gap among residents of Ghana and Senegal (Critical Journal of Social Sciences, 2026)
This work was on media usability and advancement of regional political administration. It was an appraisal of knowledge gap on regional political agenda among residents of Ghana and Senegal. The objectives was to find out the most common media of receiving information, the frequency, the barriers that affect information flow among residents of Senegal and Ghana. The theoretical framework was on Agenda setting and Social Responsibility theories. The population was taken at 52,929,398 with 384 sample size. Major findings showed that information about ECOWAs reach the people mostly through radio at 196 or 51% scores. It shows that people rely on verbal communication on regional matters.